1994
DOI: 10.1007/bf00039305
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of male sterility mutations induced in haploid sorghum tissue culture

Abstract: A high frequency of male sterile mutants regeneration was shown in callus cultures derived from leaves and panicles of haploid sorghum (Mscl, A1 cytoplasm) and a spontaneous autodiploid obtained from this haploid. The cultures derived from the embryos of this autodiploid yielded significantly fewer mutants. Absolutely or partially male sterile mutants appeared among the regenerants or in the progeny of fertile regenerants. In the self-fertilized progenies of partially male sterile mutants and in the hybrids of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…It was found that young anthers produced more callus as compared to mature anthers. A number of reports are available on studies concerning haploid sorghum culture and culture of male sterile lines (Rose et al, 1986a, b;Elkonin et al, 1987Elkonin et al, , 1993Elkonin et al, , 1994Elkonin et al, , 1995Elkonin, 1995;Elkonin andEnaleeva, 1997, 1998). Cytological analysis of meiosis in sterile plants by Elkonin and Enaleeva (1998) revealed that the tissue culture-induced mutation caused significant abnormalities in chromosome synapsis during prophase-I that resulted in the formation of multiple micronuclei during cell division.…”
Section: In Vitro Plant Regeneration Haploidy Polyploidy and Somaclmentioning
confidence: 96%
“…It was found that young anthers produced more callus as compared to mature anthers. A number of reports are available on studies concerning haploid sorghum culture and culture of male sterile lines (Rose et al, 1986a, b;Elkonin et al, 1987Elkonin et al, , 1993Elkonin et al, , 1994Elkonin et al, , 1995Elkonin, 1995;Elkonin andEnaleeva, 1997, 1998). Cytological analysis of meiosis in sterile plants by Elkonin and Enaleeva (1998) revealed that the tissue culture-induced mutation caused significant abnormalities in chromosome synapsis during prophase-I that resulted in the formation of multiple micronuclei during cell division.…”
Section: In Vitro Plant Regeneration Haploidy Polyploidy and Somaclmentioning
confidence: 96%
“…Panicles of 1-2 tillers per plants were covered using paper bag to avoid any cross pollination that might occur. At seed setting stage, number of seeds set per spikelets was counted among the R0 regenerants and fertility status of the genotypes was estimated following Elkonin et al (1994) method. Male sterile plants were recognized with the production of anthers without pollen grains dehisced on fresh receptive stigmas.…”
Section: Fertility Investigationmentioning
confidence: 99%
“…Previously, we have obtained male-sterile mutants from tissue culture of sorghum (Elkonin et al 1994). A significant influence of nuclear background on expression of induced male sterility was observed.…”
Section: Introductionmentioning
confidence: 99%